Cucumber Juice Decrease Blood Pressure on Essensial Hypertension Patient - I Ketut Sudiana; Ira Suarilah; Rusdianingseh Rusdianingseh (Universitas Airlangga, 2008)
Introduction: Essential hypertension is an intermitten or sustained elevation of dyastolic or systolic blood pressure with unkwown aetiology (idiopathic). Complication can occur such cerebro vascular accident (CVA), heart failure, arterial aneurism till death. High blood pressure should be treaten with medicine or low salt and high potassium diet. One of high potassium diet is cucumber juice. The aimed of this study was to analyze the effect of cucumber juice on blood pressure regulation. Method: A pra experimental (pre-post test one group) purposive sampling design was used in this study. Population were citizen of Pendil village who suffered essential hypertension which comprising 31 respondens. Sample were 14 respondens who met to the inclusion criteria. The independent variable was cucumber (Cucumis sativus) juice and dependent variable was blood pressure regulation. Data were analyzed by using ANOVA test with α=0.05 .Result The result showed that cucumber juice has an effect on systolic blood pressure regulation (p=0.000) after first week of treatment, systolic blood pressure regulation (p=0.000) after second week of treatment and systolic blood pressure regulation (p=0.000) from first to second week. Discussion: It can be concluded that cucumber juice consumption has an effect on blood pressure regulation among essential hypertension patients. The cucumber juice should be given in the best dose that can reduce blood pressure level, which is 2x200 g/day, as well as for treatment, it can regulate blood pressure level as long as consumed. Further studies should be developed and include the variables of stress, activities and larger responden to obtain more accurate results.